Evaluating microfoundations for aggregate price regidities: evidence from matched firm-level data on product prices and unit labor cost - Mikael Carlsson; Oskar Nordström Skans (European Central Bank (ECB), 2009)
Using data on product-level prices matched to the producing rms unit labor cost, we reject the hypothesis of a full and immediate pass-through of marginal cost. Since we focus on idiosyncratic variation, this does not t the predictions of the Mackowiak and Wiederholt (2009) version of the Rational Inattention Model. Neither do we nd that rms react strongly to predictable marginal cost changes, as expected from the Mankiw and Reis (2002) Sticky Information Model. We nd that, in line with Staggered Contracts models, rms consider both the current and future expected marginal cost when setting prices with a sum of coe cients not signicantly dierent from unity.
Keywords: D8; E3; L1; 330; business cycles; Information; Micro Data; price setting; Preisrigidität; Mikrofundierung; Preismanagement; Lohnstückkosten; Unvollkommene Information; Theorie